Pembinaan Kebermaknaan Hidup melalui Bimbingan dan Konseling Keagamaan pada Lansia di Panti Wreda Siti Khadijah Cirebon: Development of Meaningful Life through Guidance and Counseling Religion in the elderly at the Siti Khadijah Nursing Home, Cirebon - Istiqomah, Istiqomah; Kurnia, Rina (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Old age (elderly) is the last period of development in human life. Getting old is something that cannot be avoided. When entering the old age period, becoming someone who is more meaningful in life seems very important. The elderly will face various problems related to changes in physical, cognitive and psychosocial aspects. this will cause various impacts, one of which is the feeling of meaninglessness in life. Therefore, religion plays an important role in directing them to interpret life truly. Life will be meaningful if religion is used as a guide. Thus religious guidance for old age is very important because it gives parents old age to realize themselves as whole human beings in order to achieve happiness in life in this world and the hereafter. This service aims to find out and provide an understanding of the description of the meaning of life in the elderly, provide religious counseling guidance to increase the meaningfulness of the lives of the elderly and their impact on the meaningfulness of the lives of the elderly. This service uses a qualitative narrative approach through 3 stages: initial observation, implementation religious guidance and counseling, and measurement of the meaning of life. The population in this service is the elderly who live in the Cirebon Nursing Home. The sampling technique used is saturated sampling. Sampling using total sampling method as many as 4 elderly. Measurement of the meaningfulness of life in the elderly was carried out using a questionnaire in the form of a Likert scale and an interview guide. The results of the service, after carrying out religious counseling guidance for the elderly at the Kasih Ibu Nursing Home Cirebon have a meaningful life in terms of aspects of freedom of will, aspects of the will to meaning and aspects of the meaning of life experience changes significant with the average increase in the category to be high.